Prevalence and predictors of carotid artery stenosis in patients with severe aortic stenosis undergoing transcatheter aortic valve implantation. Issue 6 (10th July 2014) - Steinvil, Arie; Leshem‐Rubinow, Eran; Abramowitz, Yigal; Shacham, Yacov; Arbel, Yaron; Banai, Shmuel; Bornstein, Natan M.; Finkelstein, Ariel; Halkin, Amir
<x xml:space="preserve">Abstract</x> Objectives Our aim was to analyze the prevalence and predictors of Carotid artery stenosis (CAS) in patients undergoing transcatheter aortic valve implantation (TAVI). Background CAS is associated with the risk of periprocedural stroke in patients undergoing cardiac surgery. However, little is known about the prevalence of and clinical significance of CAS in the setting of TAVI. Methods Consecutive patients undergoing a carotid Doppler study the day before TAVI were followed prospectively. CAS was defined in accordance with current practice guidelines. Logistic regression models were used to identify independent correlates of CAS. Results The study included 171 patients (age 82 ± 6, male gender 47%). Carotid atherosclerosis (CA, defined as any carotid plaque) was present in 164 (96%) of patients, and CAS (peak systolic velocity [PSV] ≥ 125 cm/sec; ≥50% diameter stenosis) in 57 (33%) patients. Severe CAS (PSV ≥ 230 cm/sec; ≥70% stenosis, or near occlusion) was found in 15 (9%) patients. By multivariate analysis, smoking and a higher Euroscore independently predicted the presence of CAS. Patients in the present TAVI cohort had a significantly higher prevalence of both unilateral and bilateral CAS ≥ 50% than those in a previously reported cohort (n = 494 patients, age ≥ 70) undergoing clinically driven coronary angiography (33% vs. 20%, OR = 1.9, P = 0.001; and, 13% vs. 6%, OR = 2.3, P = 0.003, respectively). CAS was not independently associated with 30‐day mortality or stroke rates. Conclusions The prevalence of CAS in patients undergoing TAVI is high, exceeding that observed in patients undergoing catheterization for coronary indications. The impact of CAS on clinical outcomes following TAVI merits further research. © 2014 Wiley Periodicals, Inc.